HIGH PERFORMANCE LIQUID CHROMATOGRAPHY QUANTIFICATION OF OLEANOLIC ACID IN LAUNAEA TARAXACIFOLIA AND LARVICIDAL ACTIVITY AGAINST ANOPHELES GAMBIAE - AYIDÉ, AHOUANSOU C; JEAN-MARIE D, TOKOUDAGBA; A GABIN, ASSANHOU; URSULA, HOUNGUE; ALBAN G, HOUNGBEME; SÈDAMI R, MEDEGAN FAGLA; A FERNAND, GBAGUIDI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: One of the measures used to prevent malaria is the management of breeding sites. For preventive and ecologically profitable control, the use of bio-larvicides made from active plant extracts would be an asset for the control of malaria vectors, in particular Anopheles gambiae. Advances in pharmacognosy have revealed the benefits of several phytochemicals with very rich and varied therapeutic effects. Among the latter, oleanolic acid (OA) is quite remarkable because of its various and multiple properties, much of which is demonstrated with the leaves of Launaea taraxacifolia. Methods: After a liquid-liquid fractionation with different organic solvents of the hydro-methanolic extract of Launaea taraxacifolia, we obtained three fractions named Fhex (hexane fraction), FDCM (dichloromethane fraction) and FHM (hydro-methanolic fraction) which were tested on 3rd instar Anopheles gambiae larvae. Results: Fhex proved to be the most active with LC50 of 120.11 ppm and 69.50 ppm respectively in 24 and 48 hours of contact. We then developed a new method of Ultra-Violet High Performance Liquid Chromatography (HPLC / UV) method and determined the quantity of oleanolic acid in the Fhex and FDCM fractions to be respectively 0.46% and 0.23% . Conclusion: Launaea taraxacifolia has a larvicidal potential due to the presence of oleanolic acid whose inhibitory effect against Anopheles gambiae larvae.